Species Home-Making in Ecosystems: Toward Place-Based Ecological Metrics of Belonging - Cordell, Susan; Bardwell-Jones, Celia; Ostertag, Rebecca; Uowolo, Amanda; DiManno, Nicole (Frontiers in Ecology and Evolution, 2021)
Globalization has undeniably impacted our Earth’s ecosystems, but it has also influenced how we think about natural systems. Three fourths of the world’s forests are now altered by human activity, which challenges our concepts of native ecosystems. The dichotomies of pristine vs. disturbed -native and non-native, have blurred; allowing us to acknowledge new paradigms about how humans and nature interact. We now understand that the use of militaristic and gendered language to define the perceived role of a plant species is holding us back from the fact that novel systems (new combinations of all species) can often provide valuable ecosystem services for all creatures (including humans). In reality, ecosystems exist in a gradient from wild or native to intensely managed – and “non-nativeness” is not always a sign of a species having negative effects. In fact, there are many contemporary examples of alien species providing critical habitat for endangered species or preventing erosion in human-disturbed watersheds. In this paper, we explore the native/alien binary, the impacts of globalization and the political language of invasion through the lens of conservation biology and sociology with a tropical island perspective. This lens gives us the opportunity to offer a place-based approach towards the use of empirical observation of novel species interactions that may help in evaluating management strategies that support biodiversity and ecosystem services. Finally, we offer a site specific “metrics of belonging” approach to move forward.